(untitled) (Applied Biological Research, 2019)
A study was conducted to assess the potential of bacterial synthesized silver nanoparticles by Bacillus siralis strain UMBS1.1, isolated from a silver mine and used to remove toxicity of four textile dyes viz., Congo red, nigrosine, crystal violet and phenol red. Characterization of nanoparticles was done by UV-visible spectroscopy, FTIR, SEM and DLS analysis. Comparative dye decolourization study was carried out to degrade 25, 50, 75 and 100 ppm of each dye by both Ag-nanoparticle solution and bacterial culture preparation. Of the dyes tested, Congo red showed maximum degradation both by bacterial culture and Ag-nanoparticle solution and was selected for further study on Vigna mungo, V. radiata, Solanum lycopersicum and Viola tricolor. Results revealed 100% seed germination, both under in vitro and in vivo conditions, in all the plants tested, except S. lycopersicum (80%). The plumule length of 15.0 ± 0.23, 12.0 ± 0.23, 6.5 ± 0.22 and 5.5 ± 0.16 cm; radical length of 3.0 ± 0.17, 2.5 ± 0.20, 1.5 ± 0.17 and 1.9 ± 0.18 cm; shoot length of 24.0 ± 0.12, 17.0 ± 0.12, 23.5 ± 0.26 and 11.0 ± 0.08 cm; and root length of 2.9 ± 0.05, 3.2 ± 0.15, 2.2 ±0.15 and 3.9 ± 0.01 cm was observed in V. mungo, V. radiata, S. lycopersicum and V. tricolor, respectively, in bacterial synthesized Ag-nanoparticles treatment. Increase in seed germination and seedling growth was observed in Congo red dye with Ag-nanoparticle treatment. Thus, green synthesized Ag nanoparticles can play a vital role in bioremediation of these synthetic dyes.